The Role Of The Catholic Church Council (Station) In Religious Harmony In Klepu Village, Kec. Sooko Kab. Ponorogo - Pramono, Muhamad Fajar; Romadon, Romadon; Indallah, Sayyid Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract: The organizational role of the church council in a pluralistic environment has a very important position, especially in realizing religious harmony in the community of Klepu Village, Sook, Ponorogo. The contribution of the church council is very much needed, where Klepu Village is a village that adheres to different beliefs. Islam is the majority and Catholics make up half of the total number of Muslims. This research aims to determine the role of the church council in creating religious harmony in Klepu Village in Sooko, Ponorogo. and to find out the obstacles for the Church Council in creating religious harmony in the village. The method used in this research is an analytical/descriptive method with a Sociology of Religion approach, while data collection is carried out by observation, interviews and documentation. The results of this research explain that the existence of the church council makes a positive contribution in creating a harmonious, peaceful and tolerant Klepu community. Some of the roles of the church council which are carried out together with several formal and informal figures include inter-religious dialogue, social roles, education, and so on. This effort aims to strengthen religious harmony in Klepu and increase understanding of the harmony and religious values that exist in the Klepu village community. The obstacles for the church council are limited funds. Lack of facilities has an impact on the church council's efforts to create harmony. Sometimes there are still people who are not aware of the importance of religious harmony. However, so far there have been no serious obstacles for the church council to create religious harmony in Klepu Village.